Soil pollution mapping across Africa: potential tool for soil health monitoring - Kome, G.K.; Kundu, C.A.; Okon, M.A.; Enang, R.K.; Mesele, S.A.; Opio, J.; Asamoah, E.; Khurshid, C. (2025)
There is an urgent need for an updated and relevant soil information system (SIS) to sustainably use and manage the land across Africa. Accurate data on soil pollution is essential for effective decision-making in soil health monitoring and management. Unfortunately, the data and information are not usually presented in formats that can easily guide decision-making. The objectives of this work were to (i) assess the availability of soil pollution maps, (ii) evaluate the methodologies used in creating these maps, (iii) explore the role of soil pollution maps in soil health monitoring, and (iv) identify gaps and challenges in soil pollution mapping in Africa. Soil pollution maps across Africa are created on a local scale, with highly variable sampling size and low sampling density. The most used mapping techniques include spatial interpolation (kriging and inverse distance weighting). Among the types of soil pollutants mapped, heavy metals have received priority, while pesticides and persistent organic pollutants have received less attention. Soil pollution mapping is not incorporated within the SIS framework due to lack of reliable spatially comprehensive data and technological and institutional barriers. Current efforts remain fragmented, site-specific, and methodologically inconsistent, resulting in significant data gaps that hinder reliable monitoring and limit progress in soil pollution mapping.